(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
Under the light of Amartya Sen’s Capability Approach, this work reflects socially and legally on the Maria da Penha Law and Protection Networks for women, seeking to consider women’s substantive freedoms. To develop the theme, a qualitative and hypothetico-deductive approach is adopted, which involves the study of specialized and scientific texts, as well as updated statistical data. The results show that, although the legislation represents an important step forward, both in legal terms and symbolically, its effectiveness still faces obstacles, such as cultural barriers, resource inequality, judicial system overload, and shortcomings in the support network for victims. It is concluded that combating gender-based violence requires public policies that work in an integrated manner and aim for cultural change. These policies should help women achieve emotional, economic, social, and political autonomy so that they can fully develop their potential.